2013
DOI: 10.1371/journal.pone.0064262
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of the Proteasome Inhibitor Bortezomib (Velcade) on Ischemia-Reperfusion Injury in the Rat Retina

Abstract: PurposeTo evaluate the protective effects of bortezomib (Velcade) on ischemia-reperfusion (IR) injury in the rat retina.MethodsThe rats were randomized to receive treatment with saline, low-dose bortezomib (0.05 mg/kg), or high-dose bortezomib (0.2 mg/kg) before the induction of IR injury. Electroretinography (ERG) was used to assess functional changes in the retina. The expression of inflammatory mediators (iNOS, ICAM-1, MCP-1, TNF-α), anti-oxidant proteins (heme oxygenase, thioredoxin, peroxiredoxin), and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
(61 reference statements)
3
17
0
Order By: Relevance
“…In fact, there was minimal cell death induced in the concentration range of 0-30 nM epoxomicin. Indeed, this is in line with previous studies that demonstrate that the use of low concentrations or reversible proteasome inhibitors can induce cytoprotection to subsequent stimuli (Bardag-Gorce et al, 2011;Chen et al, 2013;Stankova et al, 2013). Only at higher concentrations (40-50 nM), when the maximum threshold for HSP70 promoter activity was reached, did significant increases in levels of cell death occur.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, there was minimal cell death induced in the concentration range of 0-30 nM epoxomicin. Indeed, this is in line with previous studies that demonstrate that the use of low concentrations or reversible proteasome inhibitors can induce cytoprotection to subsequent stimuli (Bardag-Gorce et al, 2011;Chen et al, 2013;Stankova et al, 2013). Only at higher concentrations (40-50 nM), when the maximum threshold for HSP70 promoter activity was reached, did significant increases in levels of cell death occur.…”
Section: Discussionsupporting
confidence: 91%
“…Others have demonstrated that ACR is released after I/R damage in the heart [37] and in the retina of rats [38]. Here, we first demonstrated, to our knowledge, that ACR is the main RCS formed during liver reperfusion in humans.…”
Section: Discussionsupporting
confidence: 50%
“…Santos et al (10) reported that the proteasome inhibitor MLN519 inhibits the activation of NF-κB, thus reducing the expression of inflammatory cytokines TNF-α, IL-1β and IL-6 and reducing myocardial ischemia-reperfusion injury. Chen et al (11) obtained similar results with carbobenzoxy-Leu-Leu-leucinal (MG-132). However, to the best of our knowledge, no previous study has reported on the application of proteasome inhibitors toward post-MI myocardial remodeling.…”
Section: Impact Of Proteasome Inhibitor Mg-132 On Expression Of Nf-κbmentioning
confidence: 61%
“…The present study also demonstrated that after MG-132 was applied, the expression of MMP-2 reduced in parallel with the decrease of NF-κB, IL-1β and the deposition of total collagen, type I collagen and type I/III collagen in the non-MI zone was significantly reduced, indicating that this pathway improves collagen remodeling in the non-MI zone. While previous studies reported that MG-132 attenuated myocardial hypertrophy and collagen remodeling by decreasing the expression of IL-1β, no direct evidence regarding inhibition of NF-κB was ever provided (4,11). In the present study, by measuring the gene and protein expression of NF-κB and its downstream products IL-1β and MMP-2 and analyzing their association with myocardial remodeling in the non-MI zone, it was confirmed that the mechanisms by which MG-132 inhibited post-MI myocardial remodeling included the reduction of NF-κB activation and the downregulation of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%